The Long Waves in Economic Life - Kondratieff, N. D.; Stolper, W. F. (The Review of Economics and Statistics, 1935)
I. The idea that the dynamics of economic life in the capitalistic social order is not of a simple and linear but rather of a complex and cyclical character is nowadays generally recognized. Science, however, has fallen far short of clarifying the nature and the types of these cyclical, wave-like movements. When in economics we speak of cycles, we generally mean seven to eleven year business cycles. But these seven to eleven year movements are obviously not the only type of economic cycles. The dynamics of economic life is in reality more complicated. In addition to the above-mentioned cycles, which we shall agree to call intermediate, the existence of still shorter waves of about three and one-half years' length has recently been shown to be probable.1